EXPLORING VOLITION IN PUBLIC SPEAKING CLASS AMONG THE ENGLISH EDUCATION STUDENTS IN SANATA DHARMA UNIVERSITY - Ke Lomi, Aplonia Nelci; Mbato, Concilianus Laos (English Department of Faculty of Tarbiyah and Teacher Training, 2019)
Public speaking is frequently referred to as an anxiety-provoking activity. Volition is linked to individuals' willpower and persistence to face distraction in achieving particular goals. The aim of this study is exploring the volitional strategies used by English speaking class students and the factors that particularly influenced the students in dealing with the anxiety in public speaking. The participants are the 30 public speaking class students. This study used a questionnaire and interview as the instruments for data collection. The volitional strategies found in this study are split into two kinds: action control and emotion control strategies. The factors influencing students in learning public speaking revealed are inferiority or lack of self-esteem, audience pressures, the absence of preparation, references, vocabulary; and unpredictable examination. The researcher concluded that the students show high volitional stage with their own strategies to overcome anxiety and distractions in public speaking class. This research is undertaken to encourage EFL students to overcome their anxiety and fear in speaking English.